STEPPING COLORATION OF Co(OH)2/Ni(OH)2 ELECTROCHROMIC FILM PREPARED BY A SIMPLE CHEMICAL BATH DEPOSITION METHOD - M Alvien Ghifari; Desti Riandiani; Juwita Sari; Bambang Ari Wahjoedi (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Electrochromic smart windows enable dynamic regulation of solar irradiation, thereby contributing to improved energy efficiency in building environments. In this work, Co(OH)₂/Ni(OH)₂ composite films were successfully deposited onto ITO-coated glass substrates via a facile chemical bath deposition method. Two configurations were explored: a homogeneously mixed composite and a double-layer architecture. The structural, morphological, and optical properties of the films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV–Vis spectroscopy. Both film types exhibited voltage-dependent, stepwise color modulation under applied potentials, confirming their electrochromic behavior. Notably, the mixed Co(OH)2/Ni(OH)2 film demonstrated enhanced optical modulation, with a transmittance change (ΔT) of 11.10% and an optical density change (ΔOD) of 0.09 at 0.15 V, increasing to 50.14% and 0.91 at 0.75 V. In contrast, the bilayer configuration showed significantly lower ΔT and ΔOD values of 1.36% and 0.13 at 0.15 V, and 9.64% and 0.31 at 0.75 V. These results highlight the synergistic role of Co(OH)2 in tuning the optical response of Ni(OH)₂-based electrochromic films and suggest that compositional mixing is more effective than stratified layering for optimizing optical contrast in electrochromic devices.